Mental health impact on the unmet need for family planning and fertility rate in rural Ethiopia: a population-based cohort study. (18th August 2020) - Catalao, R.; Medhin, G.; Alem, A.; Dewey, M.; Prince, M.; Hanlon, C.
Abstract: Aims: Although much research has focused on socio-demographic determinants of uptake of contraception, few have studied the impact of poor mental health on women's reproductive behaviours. The aim of this study was to examine the impact of poor mental health on women's unmet need for contraception and fertility rate in a low-income country setting. Methods: A population-based cohort of 1026 women recruited in their third trimester of pregnancy in the Butajira district in rural Ethiopia was assessed for symptoms of antenatal common mental disorders (CMDs; depression and anxiety) using Self-Reporting Questionnaire-20. Women were followed up regularly until 6.5 years postnatal (between 2005 and 2012). We calculated unmet need for contraception at 1 year ( n = 999), 2.5 ( n = 971) and 3.5 years ( n = 951) post-delivery of index child and number of pregnancies during study period. We tested the association between CMD symptoms, unmet need for contraception and fertility rate. Results: Less than one-third of women reported current use of contraception at each time point. Unmet need for birth spacing was higher at 1 year postnatal, with over half of women (53.8%) not using contraception wanting to wait 2 or more years before becoming pregnant. Higher CMD symptoms 1 year post-index pregnancy were associated with unmet need for contraception at 2.5 years postnatal in the unadjusted [odds ratio (OR) 1.09; 95% confidence interval (CI) 1.04–1.15] and fully adjusted model [OR 1.06; 95% CI 1.01–1.12]. During the 6.5 year cohort follow-up period, the mean number of pregnancies per woman was 2.4 (s.d. 0.98). There was no prospective association between maternal CMD and number of pregnancies in the follow-up period. Conclusions: CMD symptoms are associated with increased unmet need for family planning in this cohort of women with high fertility and low contraceptive use in rural Ethiopia. There is a lack of models of care promoting integration of mental and physical health in the family planning setting and further research is necessary to study the burden of preconception mental health conditions and how these can be best addressed.